2018
DOI: 10.1038/s41598-018-31406-5
|View full text |Cite
|
Sign up to set email alerts
|

Activation of hepatic stem cells compartment during hepatocarcinogenesis in a HBsAg HBV-transgenic mouse model

Abstract: Chronic infection of Hepatitis B Virus (HBV) is one of the highest risk factors of hepatocellular carcinoma (HCC). The accumulation of HBV surface antigen (HBsAg) into hepatocytes induces inflammation and oxidative stress, impairing their replicative ability and allowing the activation of the hepatic stem cells (SC) compartment. This study aimed to understand the involvement of SC during hepatocarcinogenesis in HBsAg-related liver damage, from early injury until HCC. HBsAg-transgenic (TG) and wild type (WT) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 16 publications
(22 reference statements)
3
21
0
Order By: Relevance
“…The quantification of serum ALT, AST, and LDH in all 56 animals was shown in Table 1 . As we had previously reported 14 , HBV-TG animals had a significantly higher level of serum ALT (186 ± 145 vs 47 ± 20 IU/L), AST (233 ± 133 vs 131 ± 79 IU/L), and LDH (1453 ± 339 vs 925 ± 243 IU/L) compared to WT, indicating a progressive hepatic damage in these mice.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The quantification of serum ALT, AST, and LDH in all 56 animals was shown in Table 1 . As we had previously reported 14 , HBV-TG animals had a significantly higher level of serum ALT (186 ± 145 vs 47 ± 20 IU/L), AST (233 ± 133 vs 131 ± 79 IU/L), and LDH (1453 ± 339 vs 925 ± 243 IU/L) compared to WT, indicating a progressive hepatic damage in these mice.…”
Section: Resultssupporting
confidence: 72%
“…Our previous study showed early liver inflammation caused by the HBsAg accumulation together with an increased expression of the markers of hematopoietic stem cells markers in the liver. The progression of liver damage up-regulated different CSC populations, such as EpCAM and CD133 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of several markers such as CD133, EpCAM, and CK19 were significantly increased along liver injury. Further, there was a significant correlation between CSC markers and diagnosis [21] . Furthermore, it was recently demonstrated that PreS1 of the S gene activated the expressions of CSC markers CD133, CD117, and CD90 in normal hepatocytes and HCC cells.…”
Section: Hbvmentioning
confidence: 86%
“…The HBsAg-transgenic mouse develops progressive hepatic damage due to chronic hepatitis until the onset of HCC as a result of accumulation of the HVB virus envelope protein (HBsAg) in hepatocytes [ 43 ]. HBsAg in hepatocytes induces liver regeneration due to induction of inflammation and the associated ROS, which impairs their ability to replicate and allows the activation of hepatic stem cells [ 44 ].…”
Section: Inflammation-related Carcinogenesis Model Of Each Organmentioning
confidence: 99%
“…HBsAg in hepatocytes induces liver regeneration due to induction of inflammation and the associated ROS, which impairs their ability to replicate and allows the activation of hepatic stem cells [ 44 ]. The inflammatory response of the liver in HBsAg transgenic mice includes activated resident immune cells, perivascular fibrosis, and varying degrees of steatosis but not advanced fibrosis or cirrhosis and then, the development of HCC [ 43 ].…”
Section: Inflammation-related Carcinogenesis Model Of Each Organmentioning
confidence: 99%